Modelling the Impact of Environmental and Organizational Determinants on Green Supply Chain Innovation and Performance - Rajabian Tabesh, Azadeh; Batt, Peter; Butler, Bella (Routledge, 2015)
Both customers and suppliers are becoming increasingly concerned about environmental issues in modern food chains. A firm’s decision to implement green supply chain management is based on the social objectives of the firm and its management, its desire to pursue corporate social responsibility, its relationships with channel partners, and environmental determinants such as government legislation. The speed at which green supply chain management is implemented within an organization depends on its agility and its ability to facilitate innovation. Innovation may take the form of new product development or new process development, including the introduction of environmental management systems and total quality management in both production and purchasing. This article presents a conceptual model to explain how the various theoretical constructs are related and how innovation effects green supply chain management and performance.